Ultrafast Wiggling and Jiggling: Ir2(1,8-diisocyanomenthane)42 - Pižl, Martin; Hunter, Bryan M; Greetham, Gregory M; Towrie, Michael; Záliš, Stanislav; Gray, Harry B; Vlček, Antonín (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2017)
Binuclear complexes of d8 metals (PtII, IrI, RhI,) exhibit diverse photonic behavior, including dual emission from relatively long-lived singlet and triplet excited states, as well as photochemical energy, electron, and atom transfer. Time-resolved optical spectroscopic and X-ray studies have revealed the behavior of the dimetallic core, confirming that M-M bonding is strengthened upon dσ* → pσ excitation. We report the bridging ligand dynamics of Ir2(1,8-diisocyanomenthane)42+ (Ir(dimen)), investigated by fs-ns time-resolved IR spectroscopy (TRIR) in the region of C≡N stretching vibrations, ν(C≡N), 2000-2300 cm-1. The ν(C≡N) IR band of the singlet and triplet dσ*pσ excited states is shifted by -22 and -16 cm-1 relative to the ground state due to delocalization of the pσ LUMO over the bridging ligands. Ultrafast relaxation dynamics of the 1dσ*pσ state depend on the initially excited Franck-Condon molecular geometry, whereby the same relaxed singlet excited state is populated by two different pathways depending on the starting point at the excited-state potential energy surface. Exciting the long/eclipsed isomer triggers two-stage structural relaxation: 0.5 ps large-scale Ir-Ir contraction and 5 ps Ir-Ir contraction/intramolecular rotation. Exciting the short/twisted isomer induces a ∼5 ps bond shortening combined with vibrational cooling. Intersystem crossing (70 ps) follows, populating a 3dσ*pσ state that lives for hundreds of nanoseconds. During the first 2 ps, the ν(C≡N) IR bandwidth oscillates with the frequency of the ν(Ir-Ir) wave packet, ca. 80 cm-1, indicating that the dephasing time of the high-frequency (16 fs)-1 C≡N stretch responds to much slower (∼400 fs)-1 Ir-Ir coherent oscillations. We conclude that the bonding and dynamics of bridging di-isocyanide ligands are coupled to the dynamics of the metal-metal unit and that the coherent Ir-Ir motion induced by ultrafast excitation drives vibrational dephasing processes over the entire binuclear cation.Binuclear complexes of d8 metals (PtII, IrI, RhI,) exhibit diverse photonic behavior, including dual emission from relatively long-lived singlet and triplet excited states, as well as photochemical energy, electron, and atom transfer. Time-resolved optical spectroscopic and X-ray studies have revealed the behavior of the dimetallic core, confirming that M-M bonding is strengthened upon dσ* → pσ excitation. We report the bridging ligand dynamics of Ir2(1,8-diisocyanomenthane)42+ (Ir(dimen)), investigated by fs-ns time-resolved IR spectroscopy (TRIR) in the region of C≡N stretching vibrations, ν(C≡N), 2000-2300 cm-1. The ν(C≡N) IR band of the singlet and triplet dσ*pσ excited states is shifted by -22 and -16 cm-1 relative to the ground state due to delocalization of the pσ LUMO over the bridging ligands. Ultrafast relaxation dynamics of the 1dσ*pσ state depend on the initially excited Franck-Condon molecular geometry, whereby the same relaxed singlet excited state is populated by two different pathways depending on the starting point at the excited-state potential energy surface. Exciting the long/eclipsed isomer triggers two-stage structural relaxation: 0.5 ps large-scale Ir-Ir contraction and 5 ps Ir-Ir contraction/intramolecular rotation. Exciting the short/twisted isomer induces a ∼5 ps bond shortening combined with vibrational cooling. Intersystem crossing (70 ps) follows, populating a 3dσ*pσ state that lives for hundreds of nanoseconds. During the first 2 ps, the ν(C≡N) IR bandwidth oscillates with the frequency of the ν(Ir-Ir) wave packet, ca. 80 cm-1, indicating that the dephasing time of the high-frequency (16 fs)-1 C≡N stretch responds to much slower (∼400 fs)-1 Ir-Ir coherent oscillations. We conclude that the bonding and dynamics of bridging di-isocyanide ligands are coupled to the dynamics of the metal-metal unit and that the coherent Ir-Ir motion induced by ultrafast excitation drives vibrational dephasing processes over the entire binuclear cation.